# SOLUTION: Can you show me how to solve this problem please? 8(2x-9)-3=8(x-8)+(5)

Algebra ->  Algebra  -> Linear-equations -> SOLUTION: Can you show me how to solve this problem please? 8(2x-9)-3=8(x-8)+(5)      Log On

 Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Algebra: Linear Equations, Graphs, Slope Solvers Lessons Answers archive Quiz In Depth

 Question 59426: Can you show me how to solve this problem please? 8(2x-9)-3=8(x-8)+(5)Answer by uma(370)   (Show Source): You can put this solution on YOUR website!8(2x-9) - 3 = 8(x-8) + 5 First we remove the parenthesis by multiplying the terms inside the parenthesis and the outside factor. ==> 16x - 72 - 3 = 8x - 64 + 5 ==> 16x - 75 = 8x - 59 [simplifying the values] ==> 16x - 8x = -59 + 75 [Adding 75-8x to both the sides ] ==> 8x = 16 [simplifying the like terms] ==> 8x/8 = 16/8 ==>x = 2 Good Luck!!!